The Anti-Corruption Education on the Basis of Religion and National Culture - Syarifah Gustiawati Mukri; Hidayah Baisa (Jurnal Cita Hukum, 2020)
AbstractActs of corruption have harmed many people and even tortured themselves. Corruption precaution through education way is considered not effective and encouraging since it could not eradicate corruption act which was committed by each layer of society even from educated to regular people. Moreover, it is not sufficient enough vanished with the law approach and enforcement. This study is empirical qualitative research conducted through a literature review and social reconstruction approach. Specifically, the study explains how the concept of visible anti-corruption character education on religious and national culture-based utilized as a strategic step to instill anti-corruption education among students. The results revealed that the embedding and developing students must be built upon faith and piety to Allah SWT, the optimal noble character, and being settled to the family environment. The learning concept of this notion is varied and arranged systematically, comprehensively, and proportionally according to the percentage of proposed effectiveness.Keywords: Anti-Corruption Education, Religion & National Culture AbstrakPerbuatan korupsi telah merugikan banyak kalangan dan menyengsarakan diri sendiri. Pencegahan korupsi melalui jalur pendidikan dinilai belum efektif dan menggembirakan, karena belum dapat memberantas korupsi yang dilakukan oleh lapisan masyarakat, bahkan kalangan terpelajar sampai keakar-akarnya. Pemberantasan korupsi ternyata tidak cukup pula dengan pendekatan dan penegakan hukum. Penelitian ini termasuk jenis penelitian kualitatif empiris dengan pendekatan telaah literatur dan rekonstruksi sosial. Penelitian ini menjelaskan bagaimana konsep pendidikan karakter antikorupsi berbasis agama dan budaya bangsa yang visibel, sebagai langkah strategis untuk menanamkan pendidikan antikorupsi di kalangan pelajar. Hasil penelitian menjelaskan, bahwa penanaman dan pengembangan peserta didik harus berlandaskan keimanan dan ketakwaan kepada Tuhan Yang Maha Esa, berkarakter (berakhlak mulia) secara optimal, dan telah ditanamkan lebih dahulu dalam lingkungan keluarga. Konsep pembelajarannya variatif dan disusun secara sistematis, komprehensif dan proporsional sesuai persentase efektifitas yang akan dicapai.Kata Kunci: Pendidikan Anti Korupsi, Agama & Budaya Bangsa АннотацияКоррупция нанесла вред многим людям. Предотвращение коррупции с помощью образования считается неэффективным и безнадежным, поскольку оно не смогло искоренить коррупцию, которая привержена обществом к своим корням. Оказывается, одного подхода и правоохранительных органов недостаточно для искоренения коррупции. Эта работа представляет собой качественно-эмпирическое исследование с подходом обзора литературы и социальной реконструкции. Это исследование объясняет, каким образом концепция антикоррупционного воспитания, основанная на религии и видимой национальной культуре, воспринимается как стратегический шаг к воспитанию антикоррупционного образования среди учащихся. Результаты исследования объяснили, что совершенствование и развитие учащихся должны основываться на вере и преданности Всемогущему Богу, оптимально быть человеком с характером (благородный характер) и в первую очередь внедряться в семейную среду. Концепция обучения разнообразна и организована систематически, всесторонне и пропорционально в зависимости от процента эффективности, который должен быть достигнут.Ключевые Слова: Антикоррупционное Образование, Религия и Национальная Культура.